Genetic evidence for difference between intracellular and extracellular peptides in influenza A matrix peptide-specific CTL recognition. - Matsui, M; Moots, R; Warburton, R; Peace-Brewer, A; Tussey, L; Quinn, D; Mcmichael, A; Frelinger, J (1995)
During the course of extensive mutagenesis of HLA-A2.1, we examined influenza A matrix peptide (FMP)-specific CTL recognition of HMy2.C1R (C1R) cells expressing mutant HLA-A2.1 molecules, sensitized with synthetic peptide, FMP 58-66, (exogenous peptide), or infected with influenza A virus (endogenous peptide). Most mutants showed equivalent presentation of exogenous and endogenous peptides to FMP-specific CTL. However, five of the mutants differed in this property. Two of the five mutants, F9L and T134K, present exogenous peptide to FMP-specific CTL, but fail to present endogenous peptide to CTL. Western blot analysis using anti-matrix protein Ab indicates that the matrix protein is expressed in these mutants after infection with virus. Interestingly, transfection of these two mutants with a minigene encoding FMP 58-66 results in efficient lysis by FMP-specific CTL. Peptide-binding assays demonstrate that the two mutations dramatically decrease the binding of FMP. However, these mutants bind FMP as well as wild type in the presence of exogenously added human beta 2-m, suggesting that the lower affinity for beta 2-m leads to the inability to present endogenous peptide. The remaining three mutants, Y27N, Q32K, and S132C, fail to present exogenous peptide, but present endogenous peptide to FMP-specific CTL. Pulse-chase analyses followed by endoglycosidase-H treatment show that the rate of maturation and processing of the five mutant HLA-A2 molecules in C1R cells is identical to that of wild type. Overall, this study suggests that the assembly and subsequent recognition of endogenous peptide differs from that of exogenous peptide.